Pengaruh Model Pembelajaran PjBL Terhadap Kemampuan Pemahaman Konsep Ditinjau dari Gaya Belajar - Imaniar Salwa Nabila; Dewi Azizah; Muhammad Najibufahmi (JURNAL PENA EDUKASI, 2025)
Abstract: This research is motivated by the tendency of vocational high school (SMK) students to experience difficulties in understanding mathematical concepts. Understanding mathematical concepts is an activity of comprehending and interpreting a concept to solve mathematical problems. The purpose of this study is to measure the mathematical concept understanding ability of SMK students using the Project-Based Learning (PjBL) model compared to the Problem-Based Learning (PBL) model, viewed from the perspective of learning styles. To achieve this, an experimental method was used with a quasi-experimental design in the form of a posttest-only control design. Data were collected using test instruments and questionnaires, and the data analysis technique used was two-way Anova. This study shows that: (1) The PjBL model results in better concept understanding ability than the PBL model in the topic of statistics; (2) There are differences in the effects of auditory, visual, and kinesthetic learning styles on concept understanding ability; (3) There is an interaction between learning models and learning styles on the mathematical concept understanding ability. It is concluded that the PjBL learning model has a significant effect on the mathematical concept understanding ability of vocational high school students when viewed from their learning styles.          Keywords: conceptual understanding; learning styles; PjBL; vocational high school students Abstrak: Penelitian ini dilatarbelakangi oleh adanya kecenderungan dari siswa SMK mengalami kesulitan dalam memahami konsep matematika. Pemahaman konsep matematika merupakan aktivitas dalam memahami dan menafsirkan suatu konsep untuk menyelesaikan persoalan matematika. Tujuan penelitian ini adalah untuk mengukur kemampuan pemahaman konsep matematika siswa SMK menggunakan model Project-Based Learning (PjBL) dibandingkan dengan model Problem-Based Learning (PBL) yang ditinjau dari gaya belajar. Untuk keperluan tersebut, digunakan metode eksperimen dengan design yang digunakan adalah quasi experimental design berjenis posttest only control design. Data diperoleh menggunakan intrumen tes dan angket, dan teknik analisis data yang digunakan adalah Anava dua jalur. Penelitian ini menunjukkan bahwa: (1) Model PjBL menghasilkan kemampuan pemahaman konsep yang lebih baik daripada model PBL pada materi Statistika; (2) Terdapat perbedaan efek antara gaya belajar auditori, visual, dan kinestetik terhadap kemampuan pemahaman konsep; (3) Terdapat interaksi antara model pembelajaran dengan gaya belajar terhadap kemampuan pemahaman konsep matematika. Disimpulkan bahwa terdapat pengaruh yang signifikan dari model pembelajaran PjBL terhadap kemampuan pemahaman konsep matematika yang ditinjau dari gaya belajar siswa SMK.  Kata kunci: gaya belajar; pemahaman konsep; PjBL; siswa SMK